Determinación del coeficiente de cultivo kc para frejol phasseolus vulgaris bajo invernadero en la granja Santa Inés - Cabello Alburqueque, Jimmy Fabian (2015)
As an alternative to improve the use of irrigation water is important to conduct studies for determining crop coefficients (kc), and adapt to the different areas our country taking into consideration lower aspects which is intended to produce (temperature, soil type between others), because the water requirement of the crop is essential for it to perform all its vital processes, Kc in different growth stages of the crop help improve the efficiency of irrigation systems, because they provide the cultivation only the amount of water needed, so that excess irrigation water can cause inter alia washing fertilizer and waste water itself, while a lower contribution to the needs of the crop water consumption can to cause water deficit and hence a reduction in production. The main objective of the study was to determine the curve of kc, for the cultivation of beans (Phaseolus vulgaris L.) during their growing period, under controlled greenhouse conditions. In this research I determine crop coefficients weekly generated in field cultivation and then separated by phenological phases for the determination lysimeters heavy home were used in addition to determine the water needs for each phenological phase using formulas From the ratio of certain crops. The sampling frame it 10 floors of growing beans at random to which they record the weight before and after a total of 40 experimental units for determining ETc, the ETO was obtained by the same procedure with 5 crop plants Reference grass taken at random from a total of 10 units. The results indicated that the values of Kc and the highest water needs are in the middle stage of development and that they are beginning to come down to the final stage of the crop.